The predictors of attitude towards online advertising - Kok, Adeline Li Ming *; Teoh, Boon Wai; Mazitah Hussin,; Nik Kamariah Nik Mat, (Scientific & Academic Publishing, 2013)
With the significant increase of the number of Internet users in Malaysia to 17.5 million users in 2011, on-line advertisers need to understand the consumers’ attitude towards on-line advertising better. Thus, the main aim of this research paper is to study the predictors of consumers’ attitude toward online advertising. Respondents were chosen from students studying in private education institutions in Malaysia since past studies indicate that most of these online users are young consumers. Three constructs have been identified to predict consumers attitude toward online advertising which are usability, trust and information. The research approach adopted in this study is a survey method using purposive sampling. The data was collected through self-administered distribution and received 207 valid responses. The findings of this research reveal that all the three predictors which are usability, trust and information had positive significant influence on consumers’ attitude toward online advertising.